Pengaruh Toxic Parent Terhadap Perkembangan Karakter Siswa Kelas VIII SMP Negeri 3 Tarutung Kabupaten Tapanuli Utara Tahun Pembelajaran 2022/2023 - Lisnawati Lisnawati; Rusmauli Simbolon; Adiani Hulu; Sandy Ariawan; Maryska Debora Silalahi (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The aim of this research is to determine the positive and significant influence of toxic parents on the character development of class VIII students at SMP Negeri 3 Tarutung T.A 2023/2024. The research method used is a quantitative method with descriptive statistics. The population is all 169 students in class VIII of SMP N 3 Tarutung, North Tapanuli Regency for the 2023/2024 academic year who are Protestant Christians and a sample of 32 people was determined using a purposive sampling technique. Data was collected using a positive closed questionnaire with 30 items, namely 15 items for variable ) Test analysis requirements: a) positive relationship test obtained rxy = 0.613 > rtable(=0.05,n=32) = 0.349. b) Testing a significant relationship obtained a value of tcount= 4.245 > ttable(=0.05, dk=n-2=30)= 2.042. 2) Test the effect: a) Test the regression equation, obtained the regression equation Y ̂=